Key factors of educational CRM success and institution performance: A SEM analysis - Ade Octavia; Della Raymena Jovanka; Turki Mesfer Alqahtani; Tommy Tanu Wijaya; Akhmad Habibi (Cogent Business & Management)
Customer relationship management (CRM) success is vital in today’s growing business practice, including in higher education institutions (HEIs). Within this study context, educational customer relationship management (EdCRM) is utilized to manage the interaction between educational institutions and their future and current students. This study aimed at determining the predicting role of institutional capability (IC), student orientation (SO), digital technology (DT), and facilitating condition (FC) to EdCRM success. The study also assessed FC and EdCRM success as factors affecting institution performance (IP). The instrument of the current study was adapted from prior studies and piloted; the pilot data were validated through explanatory factor analysis (EFA). The main data were gathered from 537 respondents. Partial least squares structural equation modeling (PLS-SEM) procedures were used to examine the hypotheses. Findings indicated that the EdCRM success was significantly predicted by IC, SO, and DT. Meanwhile, FC was reported to insignificantly predict EdCRM success. FC and EdCRM success strongly predicted IP. Recommendations were proposed for the betterment of EdCRM success and IP in HEIs.